An innovative rheometric tool to study chemorheology - Altobelli Annarita; Pasquino Rossana; Grizzuti Nino (Applied Rheology)
This study presents an innovative 3D-printed rheometric tool designed for the in situ analysis of phase transitions, providing a solution to the limitations of conventional rheometric methods. Standard techniques often face challenges in accurately capturing rapid gelation kinetics due to insufficient mixing capabilities and test preparation times. The new tool, adaptable to all conventional rheometers equipped with a disposable shuffle, incorporates a custom spiral channel geometry that allows immediate and efficient merging of two-component systems directly within the measurement system. The natural roughness of the 3D printed surface and the possibility of tuning plate and channel sizes make the tool even more promising. The instrument has been validated on three different systems: polyvinyl alcohol with borax, which undergoes rapid chemical gelation; sodium alginate with calcium chloride, which is characterized by rapid chemical gelation induced by ions; and Pluronic F68 solutions, which exhibit a concentration-dependent phase transition, from a crystal phase to a solution of randomly distributed spherical micelles. The 3D printed tool optimizes the study of chemorheological measurements in situ, capturing the evolution of viscoelastic properties in real time for the three cases.